City on fire - Hallberg, Garth Risk (New York Alfred A. Knopf, 2015)
The all-too-human individuals who live within this extraordinary first novel are: Regan and William Hamilton-Sweeney, estranged heirs to one of the city's biggest fortunes; Keith and Mercer, the men who, for better or worse, love them; Charlie and Sam, two Long Island teenagers seduced by downtown's nascent punk scene; an obsessive magazine reporter; his spunky, West Coast-transplant neighbor; and the detective trying to figure out what they all have to do with a shooting in Central Park. From post-Vietnam youth culture to the fiscal crisis, from a lushly appointed townhouse on Sutton Place to a derelict squat on East 3rd Street, this city on fire is at once recognizable and completely unexpected. And when the infamous blackout of July 13th, 1977 plunges it into darkness, each of these entangled lives will be changed, irrevocably
1
Keywords: Mystery fiction